Expression of the unassembled capsid protein during infection of Shigella sonnei by bacteriophage T7 results in DNA damage that is repairable by bacteriophage T3, but not T7, DNA ligase. - Beck, P J (1986)
The abortive infection of bacteriophage T7 in Shigella sonnei D2 371-48 is characterized by a premature inhibition of phage DNA replication and nucleolytic breakdown of all phage DNA. Mutations in T7 gene 10 which are recessive to the presence of the wild-type allele can alleviate the restriction of phage growth. Phage T3 productively infects S. sonnei D2 371-48, as does a T7-T3 hybrid phage that contains, in particular, a gene 10 of T7 origin. It is the presence of T3 DNA ligase that allows phage growth on S. sonnei D2 371-48, and this enzyme can also rescue wild-type T7 from the abortive infection. T7+ is therefore functionally ligase deficient during the infection of S. sonnei D2 371-48; this deficiency is a result of the expression of the phage capsid protein, but it is independent of the assembly of the protein into a procapsid or other morphogenetic structure.